Does Homeownership Partly Explain Low Participation in Supplementary Pension Schemes?. (17th January 2016) - Torricelli, Costanza; Brancati, Maria Cesira Urzì; Santantonio, Marco
Abstract : To investigate a possible trade‐off between homeownership and individual participation in a supplementary pension scheme, we use nine waves of the Bank of Italy's Survey on Household income and Wealth (1995–2012). Italy lends itself to this type of investigation because the Italian public pension system was heavily reformed in the period, providing in principle incentives for participation, and the homeownership rate is very high. The impact of homeownership is captured in two ways: by a dummy for being homeowner and by an index capturing household portfolio illiquidity due to housing. Our results show that, after controlling for a vast array of socio‐economic characteristics and allowing for unobserved individual heterogeneity, both measures of homeownership are negatively associated with participation in supplementary pension schemes. Moreover such an effect persists both in boom and bust phases of the housing market and does not disappear even after tax incentives and a strong default option introduced by the 2007 reform.